ABILITY TO RECOGNIZE THE LETTERS OF THE ALPHABET IN CHILDREN AGED 5-6 YEARS GROUP B AT AL-IQRA` KINDERGARTEN, KERUAK DISTRICT, EAST LOMBOK REGENCY - Lana Salsabila (JOETAL: Journal of Education, Teaching and Learning, 2025)
In this study, the background is research on the ability to recognize letters of the alphabet in children aged 5-6 years group B at TK Al-Iqa' Keruak District, East Lombok Regency. The purpose of this study was to determine the ability to recognize letters of the alphabet in children and the factors that influence the ability to recognize letters of the alphabet in children aged 5-6 years group B at TK Al-Iqra' Keruak District, East Lombok Regency. The method in the study used descriptive qualitative research. Data collected through observation, interviews, documentation. Data were analyzed using data reduction, data display, data verification or drawing conclusions. While the validity of the data will be strengthened by extending observations, increasing perseverance, and data triangulation. The results of this study indicate that the ability to recognize letters of the alphabet in children aged 5-6 years that with the category "Starting to Develop" (SD) as many as 7 students, 3 students with the category "Not Yet Developing" (NYD). 1 student with the category "Developing Very Well" (DVW). 3 students with the category "Developing According to Expectations" (DAE). The factors that influence the ability to recognize letters of the alphabet in children aged 5-6 years are: Internal factors, (1) Emotional conditions; (2) Memory ability; (3) Reading interest; The external factors are, (1) Playmates; (2) Parents.